Dedolomitization and alkali-silica reactions in low-expansive marbles from the province of Córdoba, Argentina - Locati, Francisco (2014)
Marbles from the province of Córdoba (Argentina) have been used as aggregates in concrete; however, there is little information about their potential reactivity and interaction with the cement paste. Recently, the alkali-carbonate reactivity of dolomitic to calcitic marbles from this province was determined by standardized methods (ASTM C1293, ASTM C586, CSA A23.2-26A) and a modification of the Chinese Accelerated Mortar Bar Method (M-CAMBT) using a single aggregate size fraction (2.5–5.0 mm). Although all samples behaved as non-reactive some expansion was recorded, especially in the M-CAMBT method. In this work microstructural and chemical studies were carried out by stereomicroscopy, polarizing microscopy, X-ray diffraction (XRD), scanning electron microscopy (SEM) and electron probe microanalysis (EPMA) on mortar bars tested by the M-CAMBT method. Dedolomitization was detected in all dolomitic and calc-dolomitic marbles being more accentuated in the samples with more dolomite. This process is characterized by the development of different zones in the cement–aggregate interface that differ in texture and chemical composition and are similar to the zones described by other authors in dolomitic limestones typically associated with the so-called alkali–carbonate reaction. Therefore, the presence and distribution of dedolomitization appears not to be related to the texture of the aggregates but to the amount of dolomite in the rock. The low expansions recorded were associated with relict strained quartz and possibly with fine-grained phlogopite in the matrix of the rocks, which have acted as silica sources for the development of secondary silicates of variable composition (±Ca ± Na ± K ± Mg ± Al) and microfissures as a result of the alkali–silica reaction rather than the non-expansive dedolomitization process.